2003
DOI: 10.1246/cl.2003.670
|View full text |Cite
|
Sign up to set email alerts
|

Stereospecific Ring-Opening Metathesis Polymerization of endo-Dicyclopentadiene by Schrock–Hoveyda Catalyst and Novel Mo- and W-based Complexes. Development of Crystalline Hydrogenated Poly(endo-dicyclopentadiene)

Abstract: Novel crystalline polymer, crystalline hydrogenated poly(endo-dicyclopentadiene), was developed on the basis of the development of new cis- and iso-specific ROMP catalysts such as MoO(rac-5,5′,6,6′-Me4-3,3′-t-Bu2-2,2′-biphenolate)2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…The use of 1/250 equiv of the 2 ‐based catalyst afforded an opaque poly(DCPD) resin, but the polymer yield was rather low (<95%). As previously reported, the catalytic activity of 1 ([DCPD]/[Catalyst] < 20,000) was 10 times higher than that of 2 ([DCPD]/[Catalyst] < 2000) in the case of solution polymerization 7(b). It is plausible that a high catalyst activity is necessary to attain rapid bulk polymerization.…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…The use of 1/250 equiv of the 2 ‐based catalyst afforded an opaque poly(DCPD) resin, but the polymer yield was rather low (<95%). As previously reported, the catalytic activity of 1 ([DCPD]/[Catalyst] < 20,000) was 10 times higher than that of 2 ([DCPD]/[Catalyst] < 2000) in the case of solution polymerization 7(b). It is plausible that a high catalyst activity is necessary to attain rapid bulk polymerization.…”
Section: Resultsmentioning
confidence: 71%
“…The stereospecific ROMP of cycloolefins has also been studied energetically for 2 decades 4–6. Recently, we have reported that molybdenum‐ and tungsten‐based catalysts bearing substituted biphenolate ligands, such as MoO( racemic ‐5,5′,6,6′‐Me 4 ‐3,3′‐ t ‐Bu 2 ‐biphenolate) 2 ( 2 ), promote cis‐ and isoselective ROMPs of endo ‐dicyclopentadiene (DCPD) and norbornene 7. More recently, cis‐ and syndio‐selective ROMP of DCPD has been accomplished with newly developed tungsten imido‐based catalysts 8…”
Section: Introductionmentioning
confidence: 99%
“…The proposed catalytic system, WCl 6 /iso-Bu 3 Al/EtOH, was highly effective for ROMP polymerization of Et-TCD and the optimal composition was found as Et-TCD/WCl 6 / (iso-Bu) 3 Al/EtOH of 500/1/3/2 in molar ratio. At this composition, the yield of p-Et-TCD reaches 100% and no gel formation is observed.…”
Section: Resultsmentioning
confidence: 93%
“…Ru complexes such as RuHCO(Cl)(PPh) 3 , RuCl 2 (PPh 3 ) 3 , RuCl 2 (PPh 3 ) 4 and third-generation Grubbs catalyst were reported as homogeneous catalysts for the hydrogenation of ROMP polymers. 4,[10][11][12] In spite of high activity of these catalysts, Ru-catalyzed hydrogenation has a serious drawback in terms of product purification due to contamination by hard-to-remove Ru complexes and low molecular weight side products formed from the polymer chain scission reaction.…”
Section: -4mentioning
confidence: 99%
“…Cyclic olefin polymer (COP) is a class of olefin‐based high performance thermoplastic resin, which has attracted intensive researches from either academic or industry in recent years. Compared with polymethylmethacrylate and polycarbonate, which are the conventional polymeric optical materials, COP possesses more attractive properties such as excellent transparency, low density, high thermal stability, low shrinkage, low moisture absorption, and low birefringence . COP materials have been applied to many areas, for instance, plastic lenses, optical storage media, drug packaging, prefillable syringes, blister packaging, and so on.…”
Section: Introductionmentioning
confidence: 99%